Social adaptation of the indigenous peoples of the Russian North to the changing ice environment. - Gashiliva , Dr. Ludmila (2011)
Dr. Ludmila Gashiliva Head of the Institute of the Peoples of the North, and Tatiana Bulgakova, Professor of the Institute of the Peoples of the North, Russian State Pedagogical University, at the NRF 6th open Assembly in Hveragerði, Iceland. September 2011.